PROBLEM BASED LEARNING DI SEKOLAH DASAR: META-SINTESIS TERHADAP KEMAMPUAN BERPIKIR KRITIS, PROBLEM SOLVING, SELF-REGULATED LEARNING, DAN INTEGRASI TEKOLOGI - Muhammad Zakki Musyafa; Rizqi Nur Amalya; Dwi Septi Rahayu; Zalfaa Zayyana; Nurlaila Ana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Problem-Based Learning (PBL) is a relevant learning model that addresses the demands of 21st-century education, emphasizing critical thinking, problem-solving, collaboration, and independent learning. This study aims to analyze the effectiveness of PBL implementation in elementary schools through a meta-synthesis approach to various research findings addressing critical thinking, problem-solving, self-regulated learning, and technology integration. The research method employed a qualitative approach with a literature review of journal articles obtained from various scientific sources. The synthesis results indicate that PBL significantly improves critical thinking skills through analysis, evaluation, argumentation, and evidence-based decision-making. Furthermore, PBL effectively develops problem-solving skills through investigation and contextual problem-solving. The implementation of PBL also contributes to improved self-regulated learning by encouraging students to plan, monitor, and evaluate their learning process independently. The integration of technology, such as interactive videos and digital learning platforms, further strengthens student engagement and supports the development of 21st-century skills. However, PBL implementation still faces challenges such as teacher preparedness, limited technological facilities, and heterogeneity in student abilities. Overall, PBL has proven effective in building an active, collaborative, reflective, and student-centered learning ecosystem to support the transformation of elementary school education.